EXPRESSION OF QUANTITATIVENESS IN PHRASEOLOGICAL UNITS WITH NUMERICAL COMPONENTS IN UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2025)
This article examines the expression of quantitativeness through phraseological units with numerical components in Uzbek and English. The study analyzes phraseological units, categorizing them into two main groups: those expressed through numbers and lexical elements. Numerical phraseological units in Uzbek and English reflect both similarities and differences, deeply rooted in cultural and linguistic characteristics. For instance, the Uzbek idiom "besh qo‘l barobar emas" and the English "two heads are better than one" showcase cultural wisdom and values. The findings reveal that phraseological units with numerical components convey a wide range of meanings, including collectivity, specification, mitigation, exaggeration, and meticulousness. This article provides a theoretical foundation for further exploration of quantitativeness in linguistics and highlights the significance of phraseological units in the linguistic and cultural context.